Farnesyl Pyrophosphate Is a Novel Pain-producing Molecule via Specific Activation of TRPV3 - Bang, Sangsu (American Society for Biochemistry and Molecular Biology, 2010)
Temperature-sensitive transient receptor potential ion channels (thermoTRPs) expressed in epidermal keratinocytes and sensory afferents play an important role as peripheral pain detectors for our body. Many natural and synthetic compounds have been found to act on the thermoTRPs leading to altered nociception, but little is known about endogenous painful molecules activating TRPV3. Here, we show that farnesyl pyrophosphate (FPP), an intermediate metabolite in the mevalonate pathway, specifically activates TRPV3 among six thermoTRPs using Ca(2+) imaging and electrophysiology with cultured keratinocytes and TRPV3-overexpressing cells. Agonistic potencies of related compounds in the FPP metabolism were ignorable. Voltage-dependence of TRPV3 was shifted by FPP, which appears to be the activation mechanism. An intraplantar injection of FPP acutely elicits nociceptive behaviors in inflamed animals, indicating that FPP is a novel endogenous pain-producing substance via TRPV3 activation. Co-culture experiments demonstrated that this FPP-evoked signal in the keratinocytes is transmitted to sensory neurons. In addition, FPP reduced TRPV3 heat threshold resulting in heightened behavioral sensitivity to noxious heat. Taken together, our data suggest that FPP is the firstly identified endogenous TRPV3 activator that causes nociception. Our results may provide useful chemical information to elucidate TRPV3 physiology and novel pain-related metabolisms.